Frequency of Irritable Bowel Syndrome in Patients Presenting with Abdominal Pain to Ayub Teaching Hospital - Ummarah Riaz, Bushra Fiaz, Hania Akbar, Muhammad Rahim, Sardar Alam, Hafizullah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
The irritable bowel syndrome (IBS) is a chronic and sometimes disabling functional bowel disorder. The Rome IV criteria, derived from a consensus process by a multinational group of experts in functional gastrointestinal disorders, constitute the current standard for diagnosing IBS. According to defecation ir in association with a change in stool frequency or form. Bloating is a common accompanying symptom. Symptoms must be chronic, occurring at least once per week, on average, in the previous 3 months, with a duration of at least 6 months. IBS is 2-4 times common in females and genetic predisposition is suggested by evidence and 33% of patients have family history of IBS. Some dietary factors and psychological issues like anxiety and stress are also associated with IBS. Objectives: The present study was conducted to determine the frequency of irritable bowel syndrome in in patients presenting with abdominal pain in gastroenterology OPD Ayub Teaching Hospital Abbottabad. Material and Methods: This Cross sectional ( descriptive) study was carried out in the Departmen t of Gastroenterology of Ayub Teaching Hospital Abbottabad from September 2018 to February 2019 .The study population was included, Presenting with abdominal pain of either gender having age between 15 to 60 years.A detailed history was taken from the patient with clinical examination was performed on each participant. IBS was diagnosed by using ROME IV criteria. Strictly exclusion criteria were followed to control the confounders Results: Mean age of the patients was 44.66±11.486 ranging from 15 to 60 years of age, mean duration of abdominal pain was 3.38±5.714 ranging from 1 to 48 months and mean duration of symptoms was 13.30±5.268 ranging from 8 to 20 days. In frequency of gender of patients there were 117(59.7%) male and 79(40.3%) female. In frequency of irritable bowel syndrome, there were 35(17.9%) had irritable bowel syndrome while 161(82.1%) had no IBS. Conclusion: The diagnosis of IBS relies on the identification of characteristic symptoms and the exclusion of other organic diseases. Management of patients with IBS is optimized by an individualized, holistic approach that embraces dietary, lifestyle, medical, and behavioral interventions. Keywords: Irritable bowel syndrome, abdominal pain